Laccase-assisted biosensing constructs – Robust modalities to detect and remove environmental contaminants - Angel M. Villalba-Rodríguez (Case Studies in Chemical and Environmental Engineering, 2022)
This review highlights the relevance of laccase-assisted cues for detecting and removing emerging contaminants (ECs). ECs are distributed in the environmental matrices due to various industrial practices and anthropogenic inputs. The discharge and long-term persistence of ECs such as micro-pollutants, endocrine disruptors (EDs), pharmaceutical compounds, hormones, and industry-related pollutants are environmental hazards and considerable risks to wildlife and humans alike. Therefore, it is needed to implement strategic measures since the traditional wastewater treatment technologies are inefficient at detecting and eliminating an array of ECs. The current technological and engineering growth offers the potential to engineer biosensing and biocatalytic devices for various applications. Such prototypes can help real-time and in-situ monitoring environmental pollutants from different industrial sectors. Also, real-time monitoring can reduce the excessive consumption of hazardous chemicals before releasing into the environment. Laccase-assisted biocatalytic cues have gained attention as an excellent candidate for quantification, monitoring, and removing pollutants. Thus, the present review has compiled recent information to extend the current knowledge on novel alternatives to detect, quantify, and treat contaminants efficiently. Also, information is gathered on laccase-assisted biosensors, immobilized-laccase-based prototypes, their role in pollution detection, and their redefining of “removal” processes.